An approach to fluoroless radiofrequency atrial fibrillation ablation - Pittet, Thaïs; Delacrétaz, Etienne; Cook, Stéphane; Vivekanantham, Hari (Frontiers in Cardiovascular Medicine, 2025)
Atrial fibrillation is the most prevalent arrhythmia with a lifetime risk of nearly 30%. It can be associated with reduced quality of life and complications such as heart failure and stroke. Pulmonary vein isolation (PVI) is the most effective treatment for rhythm control. It has initially been performed with fluoroscopic catheter guiding. The advent of three-dimensional (3D) electro-anatomical mapping has significantly reduced the need for fluoroscopy. More recently, intracardiac echography (ICE) techniques have been used to eliminate the need for x-rays. Additional advantages include providing electrophysiology lab personnel with a lead-free working environment and avoiding radiation exposure for both patients and physicians. ICE may also enhance the safety of the procedure by enabling a safe trans-septal puncture and the early recognition of cardiac tamponade. In this article, we present our approach to fluoroless radiofrequency PVI using ICE and 3D electro-anatomical mapping.